User interface design of voice controlled consumer electronics - Gamm, Stephan; Haeb-Umbach, Reinhold (Philips Journal of Research)
Today speech recognition of a small vocabulary can be realized so cost-effectively that the technology can penetrate into consumer electronics. But, as first applications that failed on the market show, it is by no means obvious how to incorporate voice control in a user interface. This paper addresses the issue of how to design a voice control so that the user perceives it as a benefit. User interface guidelines that are adapted or specific to voice control are presented. Then the process of designing a voice control in the user-centred approach is described. By means of two examples, the car stereo and telephone answering machine, it is shown how this is turned into practice.

Human Factors of a Voice-Controlled Car Stereo - Gamm, Stephan; Haeb-Umbach, Reinhold (Eurospeech, Madrid)

The Usability Engineering of a Voice-Controlled Answering Machine - Gamm, Stephan; Haeb-Umbach, Reinhold; Langmann, Det (International Symposium on Human Factors in Telecommunications, Melbourne)

Speech recognition algorithms for voice control interfaces - Haeb-Umbach, Reinhold; Beyerlein, Peter; Geller, Dieter (Philips Journal of Research)
Recognition accuracy has been the primary objective of most speech recognition research, and impressive results have been obtained, e.g. less than 0.3% word error rate on a speaker-independent digit recognition task. When it comes to real-world applications, robustness and real-time response might be more important issues. For the first requirement we review some of the work on robustness and discuss one specific technique, spectral normalization, in more detail. The requirement of real-time response has to be considered in the light of the limited hardware resources in voice control applications, which are due to the tight cost constraints. In this paper we discuss in detail one specific means to reduce the processing and memory demands: a clustering technique applied at various levels within the acoustic modelling.

Automatic Transcription of Unknown Words in a Speech Recognition System - Haeb-Umbach, Reinhold; Beyerlein, P.; Thelen, E. (ICASSP, Detroit)
We address the problem of automatically finding an acoustic representation (i.e. a transcription) of unknown words as a sequence of subword units, given a few sample utterances of the unknown words, and an inventory of speaker-independent subword units. The problem arises if a user wants to add his own vocabulary to a speaker-independent recognition system simply by speaking the words a few times. Two methods are investigated which are both based on a maximum-likelihood formulation of the problem. The experimental results show that both automatic transcription methods provide a good estimate of the acoustic models of unknown words. The recognition error rates obtained with such models in a speaker-independent recognition task are clearly better than those resulting from separate whole-word models. They are comparable with the performance of transcriptions drawn from a dictionary.

The Philips Research system for continuous-speech dictation - Steinbiss, Volker; Ney, Hermann J.; Aubert, Xavier L.; Besling, Stefan; Dugast, Christian; Essen, Ute; Geller, Dieter; Haeb-Umbach, Reinhold; Kneser, Reinhard; Meier, Hans Günter; Oerder, Martin; Tran, Bach Hiep (Philips Journal of Research)
This paper gives an overview of the Philips Research system for continuous-speech recognition. The recognition architecture is based on an integrated statistical approach. The system has been successfully applied to various tasks in American English and German, ranging from small vocabulary tasks to very large vocabulary tasks and from recognition only to speech understanding. Here, we concentrate on phoneme-based continuous-speech recognition for large vocabulary recognition as used for dictation, which covers a significant part of our research work on speech recognition. We describe this task and report on experimental results. In order to allow a comparison with the performance of other systems, a section with an evaluation on the standard North American Business news (NAB2) task (dictation of American English newspaper text) is supplied.

Continuous speech dictation - From theory to practice - Steinbiss, Volker; Ney, Hermann J.; Essen, Ute; Tran, Bach Hiep; Aubert, Xavier L.; Dugast, Christian; Kneser, Reinhard; Meier, Hans Günter; Oerder, Martin; Haeb-Umbach, Reinhold; Geller, Dieter; Hoellerbauer, W.; et al. (Speech Communication)
This paper gives an overview of the Philips research system for phoneme-based, large-vocabulary, continuousspeech recognition. The system has been successfully applied to various tasks in the German and (American) English languages, ranging from small vocabulary tasks to very large vocabulary tasks. Here, we concentrate on continuousspeech recognition for dictation in real applications, the dictation of legal reports and radiology reports in German. We describe this task and report on experimental results. We also describe a commercial PC-based dictation system which includes a PC implementation of our scientific recognition prototype. In order to allow for a comparison with the performance of other systems, a section with an evaluation on the standard Wall Street Journal task (dictation of American English newspaper text) is supplied. The recognition architecture is based on an integrated statistical approach. We describe the characteristic features of the system as opposed to other systems: 1. the Viterbi criterion is consistently applied both in training and testing; 2. continuous mixture densities are used without tying or smoothing; 3. time-synchronous beam search in connection with a phoneme look-ahead is applied to a tree-organized lexicon.

Synthesis Procedures for Self-Testable Controllers - Hellebrand, Sybille; Wunderlich, Hans-Joachim

Evaluation of Self-Testable Controller Architectures Based on Realistic Fault Analysis - Hellebrand, Sybille; Wunderlich, Hans-Joachim; Goncalves, F.; Paulo Teixeira, Joao

Partitioning of CMOS-Circuits for On-Chip IDDQ-Testing - Hellebrand, Sybille; Herzog, Maik; Wunderlich, Hans-Joachim

Towards modelling of fuzzy functions - Hüllermeier, Eyke (in Proceedings EUFIT-95 3rd European Congress on Intelligent Techniques and Soft Computing, Aachen, Germany)

Rule-based modelling in fuzzy simulation - Hüllermeier, Eyke (in Proceedings ISFL-95 International Symposium on Logic, Zürich)

Fuzzy polynomial and spline interpolation - Hüllermeier, Eyke (in Proceedings IMACS Symposium on Systems Analysis and Simulation, Berlin)

Education for Visualization-Activities of the ACM-SIGGRAPH Education Committee - Domik-Kienegger, Gitta; Owen, GS (Proceedings of the Third Eurographics Workshop on Graphics and Visualization)

Die Gründung einer GmbH - Krimphove, Dieter; Brehmer, Carsten

Rechtliche Rahmenbedingungen des deutschen und internationalen Börsentermingeschäftes Ein Leitfaden für Banken, Sparkassen, Kreditinstitute, Anlagevermittler und Kunden mit Checklisten und Hinweisen zur Durchführung einer ordnungsgemäßen Anlageberatung - Krimphove, Dieter

Konjunkturzyklen aufgrund von Investitionsinterdependenzen: Simulation und empirische Überprüfung - Hüllermeier, Eyke (Moderne Makroökonomie-Eine kritische Bestandsaufnahme)

Rearrangement by intermediate ion/neutral complexes during the McLafferty fragmentation of unsaturated ketones - Dohmeier-Fischer, Silvia; Krämer, Nicolai; Grützmacher, Hans- Friedrich (European Journal of Mass Spectrometry)

Pattern Generation for a Deterministic BIST Scheme - Hellebrand, Sybille; Reeb, Birgit; Tarnick, Steffen; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

A Distributed Computer Architecture for Qualitative Simulation based on a Multi-DSP and FPGAs - Platzner, Marco; Rinner, Bernhard; Weiss, Reinhold (Proceedings of the 3rd Euromicro Workshop on Parallel and Distributed Processing)

High-Performance Simulators Based on Multi-TMS320C40 - Brenner, Eugen; Ginthör-Kalcsics, Robert; Hranitzky, Robert; Platzner, Marco; Rinner, Bernhard; Steger, Christian; Weiss, Reinhold (Proceedings of the 5th Annual Texas Instruments TMS320 Educators Conference)

A Special-Purpose Coprocessor for Qualitative Simulation - Friedl, Gerald; Platzner, Marco; Rinner, Bernhard (Proceedings of the EURO-PAR'95 International Conference on Parallel Processing)

Parallel Qualitative Simulation - Platzner, Marco; Rinner, Bernhard; Weiss, Reinhold (Proceedings of the EUROSIM Congress)

Improving Performance of the Qualitative Simulator QSIM - Design and Implementation of a Specialized Computer Architecture - Platzner, Marco; Rinner, Bernhard (Proceedings of the PDCS International Conference on Parallel and Distributed Computing Systems)

High-Performance Qualitative Simulation on a Multi-DSP Architecture - Platzner, Marco; Rinner, Bernhard (Proceedings of the 6th International Conference on Signal Processing Applications & Technology (ICSPAT))

Design and Implementation of Adaptive Digital Filters on a Multi-TMS320C40 System - Hranitzky, Robert; Platzner, Marco (Proceedings of the 6th International Conference on Signal Processing Applications & Technology (ICSPAT))

Hydrogen interaction with Sb-terminated GaAs and InP (110) surfaces - Santos, Paulo V.; Esser, N.; Groenen, J.; Cardona, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Optical properties of Sb-terminated GaAs and InP (110) surfaces - Santos, Paulo V.; Esser, N.; Cardona, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

III-V(110) surface dynamics from anab initiofrozen-phonon approach - Schmidt, Wolf Gero; Bechstedt, F.; Srivastava, G. P. (Physical Review B)

Se/GaAs(110): energetics and structure - Schmidt, Wolf Gero; Bechstedt, Friedhelm (Surface Science)

Quasi-particle band structure of C(111)2 × 1 and C(100)2 × 1 surfaces - Kress, Clemens; Fiedler, Marion; Schmidt, Wolf Gero; Bechstedt, Friedhelm (Surface Science)

III-V(110)/Sb(1 ML): structural and dynamical properties - Schmidt, Wolf Gero; Srivastava, G.P. (Surface Science)

Geometrical and electronic structure of the reconstructed diamond (100) surface - Kress, C.; Fiedler, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Exchange reactions versus adsorption geometries for Se/GaAs(110) - Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Se/GaAs(110): Atomic and electronic structure - Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Torque capability and control of a saturated induction motor over a wide range of flux weakening - Grotstollen, H.; Wiesing, J. (IEEE Transactions on Industrial Electronics)
Keywords: Electrical and Electronic Engineering; Control and Systems Engineering

Computer aided design and modeling of high frequency magnetic components - Becker, B.; Grotstollen, H.; Heinemann, L. (Proceedings of 1995 IEEE Applied Power Electronics Conference and Exposition - APEC'95)

Simulation of power electronic circuits with principles used in wave digital filters - Fiedler, A.; Grotstollen, H. (IAS '95. Conference Record of the 1995 IEEE Industry Applications Conference Thirtieth IAS Annual Meeting)

Investigation of asymmetrical phase-shifted full bridge [power convertors] - Fiedler, A.; Grotstollen, H. (Proceedings of IECON '95 - 21st Annual Conference on IEEE Industrial Electronics)

Simulation model for ultrasonic motors powered by resonant converters - Maas, Jürgen; Ide, Peter; Fröhleke, Norbert; Grotstollen, Horst (IAS '95. Conference Record of the 1995 IEEE Industry Applications Conference Thirtieth IAS Annual Meeting)

Investigation of PWM controlled, resonant transition converters with asymmetrical duty cycle - Fröhleke, Norbert; Fiedler, A.; Grotstollen, Horst; Margaritis, Basile (Proceedings of IECON '95 - 21st Annual Conference on IEEE Industrial Electronics)

Optimal pulsewidth modulation techniques for high-power voltage-source inverter - Sun, Jian

Hermann Ulrici (1806–1884). Der Hallesche Philosoph und die englische Algebra der Logik. Mit einer Auswahl von Texten Ulricis zur Logik und einer Bibliographie seiner Schriften - Peckhaus, Volker
Rezensionen: Philosophischer Literaturanzeiger 49 (1996), 325–328 (U. Dathe); Studia Logica 58 (1997), 335–337 (Roman Murawski); Modern Logic 8 (2000/01), 109–111 (H. Frank)

The Genesis of Grelling’s Paradox - Peckhaus, Volker (Logik und Mathematik. Frege-Kolloquium Jena 1993)
Abstract: Philosopher’s Index 30.2 (Sommer 1996), 215.

Hilberts Logik. Von der Axiomatik zur Beweistheorie - Peckhaus, Volker (NTM. Internationale Zeitschrift für Geschichte und Ethik der Naturwissenschaften, Technik und Medizin N.F.)
Rezension: Zbl. Math. 908.01010 (V.V. Pambuccian).

A Systematic Approach to State Feedback Controller Design for DC/DC Line-Side Traction Converters - Böcker, Joachim; Endrikat, Christian; Liu, Steven (EPE’95, Sevilla)

Netzkupplungsumrichter Jübek – Regelung - Janning, Jörg; Böcker, Joachim; Anbuhl, Kay; Boni, Marco (Elektrische Bahnen)

Grundprobleme der großen Philosophen. Philosophie der Neuzeit VI. Tarski, Reichenbach, Kraft, Gödel, Neurath. ed. Josef Speck, Vandenhoeck & Ruprecht: Göttingen 1992 (= Uni-Taschenbücher; 1654) - Peckhaus, Volker (Modern Logic)

“Russell y las ‘Paradojas’” [Rez. v. Alejandro R. Garciadiego, Bertrand Russell and the Origins of the Set-theoretic ‘Paradoxes’. Birkhäuser Verlag: Basel/Boston/Berlin 1992] - Peckhaus, Volker (Mathesis (México))

André Weil, Lehr- und Wanderjahre eines Mathematikers. aus dem Französischen von Theresia Übelhör, Birkhäuser Verlag: Basel/Boston/Berlin 1993 - Peckhaus, Volker (Berichte zur Wissenschaftsgeschichte)

Kurt Grelling - Peckhaus, Volker (Modern Logic Calendar 1995)

Density-functional theory and the v-representability problem for model strongly correlated electron systems - Schindlmayr, Arno; Godby, Rex William (Physical Review B)
Inspired by earlier work on the band-gap problem in insulators, we reexamine the treatment of strongly correlated Hubbard-type models within density-functional theory. In contrast to previous studies, the density is fully parametrized by occupation numbers and overlap of orbitals centered at neighboring atomic sites, as is the local potential by the hopping matrix. This corresponds to a good formal agreement between density-functional theory in real space and second quantization. It is shown that density-functional theory is formally applicable to such systems and the theoretical framework is provided. The question of noninteracting v representability is studied numerically for finite one-dimnsional clusters, for which exact results are available, and qualitatively for infinite systems. This leads to the conclusion that the electron density corresponding to interacting systems of the type studied here is in fact not noninteracting v representable because the Kohn-Sham electrons are unable to reproduce the correlation-induced localization correctly.

A Formal Definition of an Abstract VHDL'93 Simulator by EA-Machines - Börger, Egon; Glässer, Uwe; Müller, Wolfgang (Semantics of VHDL)
We present a rigorous but transparent semantic definition for VHDL corresponding to the IEEE VHDL’ 93 standard [68, 9, 84]. Our definition covers the full behavior of signal and variable assignments as well as the behavior of the various wait statements including delta, time, and postponed cycles. We consider explicitly declared signals, ports, local variables, and shared variables. Our specification defines an abstract VHDL ’ 93 interpreter in the form of transition rules for an evolving algebra machine (EA-Machine) [60]. It faithfully reflects and supports the view of simulation given in the IEEE VHDL ’ 93 standard language reference manual. The definition can be understood without any prior formal training. We illustrate our definition by running the example VHDL program set out in the Introduction to this volume.
Keywords: Transition Rule Formal Verification Variable Assignment Kernel Process Simulation Cycle

[Rez. v.] Friedrich Jaeger: Bürgerliche Modernisierungskrise und historische Sinnbildung. Kulturgeschichte bei Droysen, Burckhardt und Max Weber. Göttingen. Vandenhoeck & Ruprecht 1994 - Süßmann, Johannes (Archiv für Sozialgeschichte)

Built-In Test for Circuits with Scan Based on Reseeding of Multiple-Polynomial Linear Feedback Shift Registers - Hellebrand, Sybille; Rajski, Janusz; Tarnick, Steffen; Venkataraman, Srikanth; Courtois, B. (IEEE Transactions on Computers)

Pattern Generation for a Deterministic BIST Scheme - Hellebrand, Sybille; Reeb, Birgit; Tarnick, Steffen; Wunderlich, Hans-Joachim (ACM/IEEE International Conference on Computer Aided Design (ICCAD'95))

́Ich wäre gerne ein Engel ́. Zu Peter Roos' Demaskerade seines als Kunstwerk verkleideten Geschlechtskörpers - Öhlschläger, Claudia; Bettinger, Elfi (Maskeraden. Geschlechterdifferenz in der literarischen Inszenierung)

Zur Blickpunktbezogenheit sprachlicher Lokalisationen: Der Genese-Effekt - Buhl, Heike M.

Zur blickpunktbezogenen Wissensrepräsentation: Der Richtungseffekt - Herrmann, Theo; Buhl, Heike M.; Schweizer, Karin (Zeitschrift für Psychologie)

Rezension zu Susanne Lummerding: "Weibliche" Ästhetik? Möglichkeiten und Grenzen einer Subversion von Codes. Wien: Passagen 1994 - Öhlschläger, Claudia (Rundbrief Frauen in der Literaturwissenschaft 44: Zensur. Mai 1995)

Orientation and Motion of Tetrahydrofuran in Graphite Intercalation Compounds: Proton NMR Studies of Cs(THF)1.3C24 and K(THF)2.5C24 - Schmidt, Claudia; Rosen, M. E.; Caplan, D. F.; Pines, A.; Quinton, M. F. (The Journal of Physical Chemistry)
Keywords: Physical and Theoretical Chemistry; General Engineering

Shear-Induced Alignment of a Hexagonal Lyotropic Liquid Crystal as Studied by Rheo-NMR - Lukaschek, Michail; Grabowski, David A.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Amphiphilic liquid-crystalline networks — phase behavior and alignment by mechanical fields - Fischer, Peter; Schmidt, Claudia; Finkelmann, Heino (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Philosophinnen in der Frauenforschung. Ein Plädoyer für Vernunft und Wissenschaft - Hagengruber, Ruth Edith (Wissenschaftliche Weiterbildung für Frauen)

Amortisation und Herrschergedenken im Burgund des 15. Jahrhunderts - Kamp, Hermann (Memoria als Kultur)

Computergestützte Intervention bei Rechtschreibschwäche: Effekte eines kognitions- und lernpsychologisch orientierten Trainingsprogramms auf Morphembasis bei sehr schwachen Sonderschülern. - Walther, J.; Bigga, Regine; Bischof, H. (Sonderpädagogik)

Conformance Tests of Very Large STEP Files - Lehrenfeld, Georg; Müller, Wolfgang; Wiechers, N. (Proceedings of the 4th EXPRESS User's Group)

Pen-based Interfaces for Engineering Environments - Zhao, R.; Kaufmann, H. J.; Kern, T.; Müller, Wolfgang

Transforming SDL Diagrams Into a Complete Visual Representation - Lehrenfeld, Georg; Müller, Wolfgang; Tahedl, C. (Proceedings of Symposium on Visual Languages)
We investigate a translation of SDL diagrams into the complete visual representation of Pictorial Janus (PJ) programs in order to analyze the specification by visual debugging and animation. We additionally introduce timing concepts to PJ (Timed PJ) for a mapping of the SDL timing statements. The concepts transforming SDL interaction and process diagrams into Timed PJ are outlined by an example sketching the transformation of an Ethernet CSMA/CD protocol specification.
Keywords: Animation; Timing; Debugging; Ethernet networks; Multiaccess communication; Protocols; Computer languages; Prototypes; Environmental management; Visualization

Validation of EXPRESS Models - Müller, Wolfgang; Lehrenfeld, Georg; Wiechers, N.

SINGLE-STAGE AND DOUBLE-STAGE ACOUSTOOPTICAL TI-LINBO3 TE-TM CONVERTERS USED IN WAVELENGTH-SELECTIVE POLARIMETER AND POLARIZATION-INDEPENDENT DEPOLARIZER - REHAGE, M; Noé, Reinhold; HARIZI, C; RICKEN, R (FIBER OPTIC NETWORK COMPONENTS)

Weibliche" Ästhetik? Möglichkeiten und Grenzen einer Subversion von Codes - Öhlschläger, Claudia (Rundbrief Frauen in der Literaturwissenschaft)

Guide to EXPRESS-P - Müller, Wolfgang; Felser, W.; Buijs, F. (Proceedings of the 4th EXPRESS User's Group)
Greenville, South Carolina

Complete Visual Specification and Animations of Protocols - Müller, Wolfgang; Lehrenfeld, Georg; Tahedl, C. (Proceedings of ASP-DAC'95/CHDL'95/VLSI'95 with EDA Technofair)
This article discusses the application of Pictorial Janus (PJ) for the rapid development and analysis of protocols by animation and complete visualization. In order to make PJ applicable in the context of hardware description we first extend PJ by timing facilities (Timed PJ) and introduce an approach for integrating VHDL models into this visual framework preserving the simulation semantics of VHDL. We finally give the example of the specification and animation of a non interlocked protocol.
Keywords: Animation; Protocols; Timing; Computer languages; Electronic mail; Context modeling; Visualization; Control systems; Flow graphs; Trademarks

An Editor for the Rapid Prototyping of EXPRESS-G Models - Zhao, R.; Müller, Wolfgang; Kaufmann, H. J.; Kern, Th.; Buijs, F. (Proceedings of the 5th EXPRESS User's Group)

The Process Modeling Language EXPRESS-P - Müller, Wolfgang; Felser, W.; Wiechers, N.

MULTISTAGE SPECTRAL POLARIMETER WITH GREATER-THAN-28DB STOPBAND ATTENUATION - Noé, Reinhold; REHAGE, M; TIAN, F (ELECTRONICS LETTERS)

Azimuthal Anchoring Energy in Photoinduced Anisotropic Films - Vorflusev, Valery P.; Kitzerow, Heinz-Siegfried; Chigrinov, Vladimir G. (Japanese Journal of Applied Physics)
Most electrooptic effects in liquid crystals require a uniform orientation of the director at the glass substrates. A new method to produce suitable alignment layers is based on the creation of anisotropic polymer films by photopolymerization with linearly polarized light. In the present paper we report on measurements of the anchoring strength of these photo-induced anisotropic films. Using a wedge-cell technique, we find an azimuthal anchoring energy of W ϕ ≈2.3·10 -6 J/m 2 .
Keywords: General Physics and Astronomy; General Engineering

Convolution algebras which are not necessarily positivity-preserving - Rösler, Margit (Applications of Hypergroups and Related Measure Algebras)

Trigonometric convolution structures on Z derived from Jacobi polynomials - Rösler, Margit (Journal of Computational and Applied Mathematics)
Keywords: Applied Mathematics; Computational Mathematics

On the dual of a commutative signed hypergroup - Rösler, Margit (Manuscripta Mathematica)
Keywords: General Mathematics

Classiker und Novitäten. Zur Entwicklung des Konzertrepertoires im 19. Jahrhundert - Grotjahn, Rebecca (Zwischen Wissenschaft und Kunst. Festgabe für Richard Jakoby)

Über die Berechnung von Teilkörpern algebraischer Zahlkörper (Diplomarbeit) - Klüners, Jürgen

Conjugated Polymers for CMOS Compatible Applications - Muller, J.; Mankowski, V.; Hilleringmann, Ulrich; Goser, K.; Holmes, A.; Gelsen, O.; Stern, R. (ESSDERC ’95: Proceedings of the 25th European Solid State Device Research Conference)

Vorwort. "Postmodern(e) wahrnehmen" - was soll das? - Schroeter-Wittke, Harald; Beuscher, Bernd; Sistermann, Rolf (Prozesse postmoderner Wahrnehmung. Kunst - Religion - Pädagogik)

Coherent effects induced by static and time-dependent electric fields in semiconductors - Meier, Torsten; von Plessen, G.; Thomas, P.; Koch, S.W. (Physical Review B)
Coherent effects are analyzed that are induced by homogeneous electric fields in photoexcited semiconductors. Extended semiconductor Bloch equations are presented, which include the applied electric field, in addition to the many-body Coulomb contributions in the time-dependent Hartree-Fock approximation. These equations are solved for a one-dimensional tight-binding model of a semiconductor superlattice. Linear and nonlinear optical signals associated with the coherent field-induced effects are calculated. For the case of a static electric field, the influence of the Coulomb interaction, which is treated on the Hartree-Fock level for a contact potential approximation, on the Bloch oscillations, and on their counterpart in the frequency domain, the Wannier-Stark-ladder, is analyzed. For a time-dependent electric field, dynamic localization, i.e., the localization of electrons due to an oscillating electric field, is analyzed. It is predicted that the dynamic localization should be observable in semiconductor superlattices even in the presence of Coulomb interaction.

Polarization selection rules for quantum beating between light-and heavy-hole excitons in GaAs quantum wells - Meier, Torsten; Smith, G.O.; Mayer, E.J.; Heuckeroth, V.; Kuhl, J.; Bott, K.; Schulze, A.; Bennhardt, D.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (Solid state communications)
We report results on selection rules and polarization conditions for quantum beating between light hole and heavy hole excitons in GaAs quantum wells. The measurements were conducted using time-integrated degenerate-four-wave-mixing in a three-pulse configuration. By choosing particular polarization configurations of the ultrashort optical pulses exciting heavy and light hole excitons simultaneously, degenerate four-wave-mixing signals show either quantum beating or no modulation at all. The experiments are analyzed using a model that takes into account exciton/exciton interaction.

Dynamic Localization in Anisotropic Coulomb Systems: Field induced Crossover of the Exciton Dimension - Meier, Torsten; Rossi, F.; Thomas, P.; Koch, S.W. (Physical review letters)
The effective dimensionality of excitons can be drastically changed by applying an alternating electric field. On the basis of a full three-dimensional description of both coherent and incoherent phenomena in anisotropic structures it is found that appropriate applied oscillating fields change the exciton wave function from anisotropic three dimensional to basically two dimensional. This effective-dimension change is caused by dynamic localization which leads to an increase of the exciton binding energy and of the corresponding oscillator strength.

Theory of quasi-equilibrium nonlinear optical absorption in semiconductor superlattices - Meier, Torsten; Je, K.-C; Rossi, F.; Koch, S.W. (Applied physics letters)
Quasiequilibrium nonlinear optical absorption spectra are computed for semiconductor superlattices. The theory generalizes the semiconductor Bloch equations to describe anisotropic structures. The equation for the interband polarization is solved numerically and the carrier‐density dependent optical nonlinearities are computed. Starting from excitonic absorption, with increasing density exciton saturation and the development of gain is observed. The dependence of the gain spectra on structural parameters of the superlattice is discussed.

Transient degenerate four-wave-mixing on excitons in GaAs quantum wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Bott, K.; Schulze, A.; Heuckeroth, V.; Heller, O.; Cundiff, S.T.; Bennhardt, D.; Koch, S.W.; Thomas, P.; et al. (Laser Physics)

Biexciton Contributions to the Excitonic Nonlinearity in GaAs Quantum Wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Schulze, A.; Bennhardt, D.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (Proceedings of the 22nd International Conference on the Physics of Semiconductors ICPS)

Coherent dynamics of exciton wave packets in quantum wells and superlattices - Meier, Torsten; Feldmann, J.; Koch, M.; von Plessen, G.; Stolz, W.; Thomas, P.; Göbel, E.O. (Proceedings of the 22nd International Conference on the Physics of Semiconductors ICPS)

Polarization dependence of beating phenomena at the energetically lowest exciton transition in GaAs quantum wells - Meier, Torsten; Mayer, E.J.; Smith, G.O.; Heuckeroth, V.; Kuhl, J.; Bott, K.; Schulze, A.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (Physical Review B)
We report time-resolved degenerate four-wave-mixing experiments on a high-quality single GaAs quantum well. The signals for parallel and cross-polarized exciting pulses show pronounced quantum beats with different frequencies corresponding to the heavy/light-hole splitting and the biexciton binding energy, respectively. Comparison of the experimental data with solutions of the optical Bloch equations for a phenomenological model system shows that these features result from strong contributions of the biexcitonic state. The importance of biexcitons to the nonlinear coherent response of the two-dimension exciton is further confirmed by the frequency dependence of the time-integrated four-wave-mixing signal amplitudes measured for the two polarization geometries.

Das geht zu z/weit. Frömmigkeit und Blasphemie als Problem theologischer Ästhetik - Schroeter-Wittke, Harald (Frömmigkeit und Freiheit. Theologische, ethische und seelsorgerliche Anfragen. Hans-Dieter Bastian zum 60. Geburtstag)

Sounds of Silence. Popmusikalische Kontrapunkte zu Elia - Schroeter-Wittke, Harald; Fermor, Gotthard (Was suchst du hier, Elia? Ein hermeneutisches Arbeitsbuch)

Bist du's Elia? Streiflichter zum homiletischen Gebrauch der Elia-texte im 20. Jahrhundert - Schroeter-Wittke, Harald (Was suchst du hier, Elia? Ein hermeneutisches Arbeitsbuch)

Mit Elia Gottesdienst feiern. Anregungen zur liturgischen Gestaltung von Elia-Texten - Schroeter-Wittke, Harald (Was suchst du hier, Elia? Ein hermeneutisches Arbeitsbuch)

Was suchst du hier, Elia? Ein hermeneutisches Arbeitsbuch. Werner H. Schmidt und Horst Seebass zum 60. geburtstag

Animation zum Schlafen. Predigt (Mk 4,26-29) - Schroeter-Wittke, Harald (Zeitschrift für Gottesdienst und Predigt)

Ostern/Osterfest/Osterpredigt II. Osterpredigt - Schroeter-Wittke, Harald (Theologische Realenzyklopädie)